A population database study of outcomes associated with vitamin K antagonists in atrial fibrillation before DOAC. (28th December 2015) - Blin, Patrick; Dureau‐Pournin, Caroline; Lassalle, Regis; Abouelfath, Abdelilah; Droz‐Perroteau, Cécile; Moore, Nicholas
Abstract : Aims: This study aimed to describe the real‐life incidence of bleeding, arterial thrombotic events and death during vitamin K antagonist (VKA) treatment in atrial fibrillation (AF). Methods: This was a cohort study in Echantillon Généraliste de Bénéficiaires, the 1/97 sample of the French national healthcare claims and hospitalization database, of new VKA users with definite or probable AF and no other indication, and of patients without AF, from 2007 to 2011. Prespecified outcomes were all‐cause death, hospitalization for bleeding, arterial thrombotic event (ATE), or acute coronary syndrome (ACS) or any of the above (composite outcome). Results: Of 8894 new VKA users, 3345 had probable or certain AF, 51.7% were male, mean age was 75.1 years, 87.1% had a CHA2 DS2 ‐VASc score ≥ 2 and 11.6% a HAS‐BLED score > 3. Among AF patients, during VKA exposure the incidence rate of bleeding was 2.8 [95% confidence interval (CI) 2.2, 3.4] per 100 patient‐years, including 0.6 (95% CI 0.3, 0.8) cerebral, 1.0 (95% CI 0.7, 1.3) digestive and 1.4 (95% CI 1.0, 1.7) other bleeds. There were 1.6 (95% CI 1.2, 2.0) ACS, 1.5 (95% CI 1.1, 1.8) ATE and 3.8 (95% CI 3.2, 4.4) deaths per 100 patient‐years. The incidence rate of the composite outcome was 9.1 per 100 patient‐years (95% CI 8.2, 10.0). When patients stopped VKA, bleeding decreased (RR 0.67, 95% CI 0.43, 1.04)), but death or thrombosis increased (RR 3.06, 95% CI 2.46, 3.81 and 1.75, 95% CI 1.14, 2.70, respectively). During VKA exposure non‐AF patients had similar rates of bleeding, but fewer deaths, ACS and ischaemic events. Conclusions: Real‐life rates for bleeding, arterial thrombotic events, ACS and deaths in AF patients treated with VKA were similar to those observed in clinical trials.